2010
DOI: 10.1021/jp912195j
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Experimental Evidence for a Nonmonotonous Structural Evolution with Composition in the Molten LiF−ZrF4 System

Abstract: We propose in this paper an original approach to study the structure of the molten LiF-ZrF(4) system up to 50 mol % ZrF(4), combining high-temperature nuclear magnetic resonance (NMR) and extended X-ray absorption fine structure (EXAFS) experiments with molecular dynamics (MD) calculations. (91)Zr high-temperature NMR experiments give an average coordination of 7 for the zirconium ion on all domains of composition. MD simulations, in agreement with EXAFS experiments at the K-edge of Zr, provide evidence for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 58 publications
9
61
1
Order By: Relevance
“…The intensity of this first peak slowly increases with the YF 3 concentration. This evolution is linked to the slow increase in average CN discussed just above and shown in the bottom panel of fluorozirconates 34,42,47 . Such a structural feature, which denotes some medium-range, network-like ordering, has been shown to impact importantly the transport properties in molten fluorides.…”
Section: Microscopic Structurementioning
confidence: 78%
“…The intensity of this first peak slowly increases with the YF 3 concentration. This evolution is linked to the slow increase in average CN discussed just above and shown in the bottom panel of fluorozirconates 34,42,47 . Such a structural feature, which denotes some medium-range, network-like ordering, has been shown to impact importantly the transport properties in molten fluorides.…”
Section: Microscopic Structurementioning
confidence: 78%
“…This allowed us to predict heat-transport properties of LiFNaF-KF and NaF-ZrF 4 mixtures 38 in order to evaluate their suitability to serve as primary coolant in the advanced high-temperature reactor concept. 92 Our simulations were also used to interpret EXAFS and NMR experimental data on fluorozirconate melts 93 and to calculate electrical conductivities 94 , diffusion coefficients 95 and internal mobilities 96 .…”
Section: Obtaining the Parameters From Force-matching And Multipmentioning
confidence: 99%
“…Recent structural studies on rare earth/actinide (and analogous cations) alkali fluoride mixtures have shown that the liquid behaves like a labile network. 39,40,41,42 On the reverse, molten alkali fluorides and their mixtures typify basic molten salts. Their viscosity is known to be of the same order of magnitude than liquid water, which means that these liquids are highly fluid.…”
Section: Introductionmentioning
confidence: 99%